Cryopreserved human alternatively activated macrophages promote resolution of acetaminophen-induced liver injury in mouse - Maria Elena Candela; Melisande Addison; Rhona Aird; Tak-Yung Man; Jennifer A. Cartwright; Candice Ashmore-Harris; Alastair M. Kilpatrick; Philip J. Starkey Lewis; Anna Drape; Mark Barnett; Donna Mitchell; Colin McLean; et al. (npj Regenerative Medicine)
Abstract Acute liver failure is a rapidly progressing, life-threatening condition most commonly caused by an overdose of acetaminophen (paracetamol). The antidote, N-acetylcysteine (NAC), has limited efficacy when liver injury is established. If acute liver damage is severe, liver failure can rapidly develop with associated high mortality rates. We have previously demonstrated that alternatively, activated macrophages are a potential therapeutic option to reverse acute liver injury in pre-clinical models. In this paper, we present data using cryopreserved human alternatively activated macrophages (hAAMs)—which represent a potential, rapidly available treatment suitable for use in the acute setting. In a mouse model of APAP-induced injury, peripherally injected cryopreserved hAAMs reduced liver necrosis, modulated inflammatory responses, and enhanced liver regeneration. hAAMs were effective even when administered after the therapeutic window for NAC. This cell therapy approach represents a potential treatment for APAP overdose when NAC is ineffective because liver injury is established.